THE INFLUENCE OF UTILITARIAN AND HEDONIC DIMENSIONS ON CUSTOMER SATISFACTION WITH INTERNET BANKING - Diana Fajarwati; Wulan Setyo Astutik; Dwi Putranto Hadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Technological advancement has driven banks to innovate digital services such as internet banking to meet customers' demands for secure, convenient, and efficient transactions. The study investigates the influence of utilitarian attributes (security, perceived usefulness, perceived ease of use) and hedonistic attributes (design, social influence, enjoyment) on customer satisfaction, and the mediating influence of satisfaction on the relation between trust and user loyalty to MyBCA. Employing a quantitative approach of purposive sampling, data were collected through a validated questionnaire administered to 220 mobile banking users in the Greater Jakarta area. Data were analyzed by employing Structural Equation Modeling (SEM) using SmartPLS. The findings reveal that security, perceived usefulness, design, and trust significantly influence customer satisfaction, while perceived ease of use, social influence, and enjoyment do not. Also, customer trust enhances loyalty directly and indirectly through satisfaction, and satisfaction also strengthens loyalty. These results emphasize the importance of enhancing system security and easy-to-use application design as strategies to maintain and enhance customer loyalty in mobile banking services.